2017
DOI: 10.20902/ijptr.2017.10320
|View full text |Cite
|
Sign up to set email alerts
|

Functionality Advancement of Poorly Soluble Drug by Comparative Study of Solubilizing Techniques with Molecular Simulation to in vivo evaluation

Abstract: :This study aimed at the functionality advancement of poorly soluble model drug i.e. Cefixime with HPBCD using comparative study of different solubility enhancement methods. CFX formulations with hydroxypropyl-β-cyclodextrin (HP-β-CD) prepared by different solubility enhancement methods viz.,physical mixture, kneading method, solvent evaporation, spray drying, lyophilization/freeze drying, microwave irradiation method and compared their solubility enhancement as well as dissolution. The optimized complexes cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…X-ray powder diffraction (PXRD) study was carried out to confirm the formation of a new solid system. The diffraction pattern of ZPR showed several sharp high-intensity peaks at diffraction angles (2θ) of 10.6, 12.2, 16.3, 24.2, 25.2, and 27.1° indicating its crystalline nature [25]. The X-ray diffractograms of β-CD also showed several intense peaks due to its crystalline nature.…”
Section: Powder X-ray Diffractionmentioning
confidence: 98%
See 1 more Smart Citation
“…X-ray powder diffraction (PXRD) study was carried out to confirm the formation of a new solid system. The diffraction pattern of ZPR showed several sharp high-intensity peaks at diffraction angles (2θ) of 10.6, 12.2, 16.3, 24.2, 25.2, and 27.1° indicating its crystalline nature [25]. The X-ray diffractograms of β-CD also showed several intense peaks due to its crystalline nature.…”
Section: Powder X-ray Diffractionmentioning
confidence: 98%
“…ZPR has a pKa value of 6.5 and it is poorly water-soluble (0.007 mg/mL at 37 °C) and highly lipophilic [23]. Many researchers have tried different methods to improve the solubility of ZPR by modifying the physicochemical characteristics like nanocrystal approach by the process of media milling [23,24], solid dispersion technique using carriers like soluplus, pluronic, hydroxypropyl β-CD, sulfobutyl ether β-CD, β-CD [24][25][26][27][28] and self-nano emulsifying pellets [29].…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude of the difference between the two approaches (Pluronic—solid dispersion and β-CD—IC) was not due to the ability of the Pluronic to enhance permeation, but only to its ability to improve solubility [ 80 ]. Another study found that the spray-drying method achieved the greatest solubility improvement of the cefixime complex with HP-β-CD compared to other methods, including solvent evaporation, co-grinding, microwave irradiation, and freeze-drying [ 81 ]. These studies showed that the binary system of cefixime showed greater antimicrobial activity against S. aureus and E. coli than cefixime alone.…”
Section: Beta-lactam Antibioticsmentioning
confidence: 99%